2018
DOI: 10.21608/pssjn.2018.52552
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Women's Satisfaction During Labor Experience

Abstract: Background:Childbirth satisfaction provides a feedback for the evaluation of nursing care and determination of the quality of nursing services. The aim of the current study was to assess factors affecting women's satisfaction during labor experience. A descriptive design was adopted in the current study. Setting: the study was conducted at labor ward in Mansoura city hospitals during the period from June, 2014 to December, 2014. Sample of 214 laboring women were recruited to participate in this study. Two tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Otherwise, the study indicated that two fifths of women were not satisfied with the services at night in the ward and the majority of them were not satisfied about staff nurses' not devoting enough time to the patients. This finding was inconsistent with an earlier study conducted by Elgazzar & Hashem (2018) on Egyptian women who found that slightly more than twothirds of the women surveyed were pleased with the contact from nurses.…”
Section: Discussioncontrasting
confidence: 98%
“…Otherwise, the study indicated that two fifths of women were not satisfied with the services at night in the ward and the majority of them were not satisfied about staff nurses' not devoting enough time to the patients. This finding was inconsistent with an earlier study conducted by Elgazzar & Hashem (2018) on Egyptian women who found that slightly more than twothirds of the women surveyed were pleased with the contact from nurses.…”
Section: Discussioncontrasting
confidence: 98%
“…Notably, studies from both Egypt and Jordan provide conflicting inter and intra-country findings of women's perceptions of empathy and kindness from providers. Abdel Ghani and Berggren, Monazea and Al-Attar, and Elgazzar et al reported that two-thirds of participants in Egypt prioritized the need for nurses to demonstrate empathy in care while two other studies support this as 39.1% ( n = 435) and 37.4% ( n = 214) were dissatisfied due to poor emotional support from nurses ( 34 , 62 , 63 ). Another study in Egypt ( n = 501) found that about 75% of respondents were treated kindly/friendly by health workers, but about half felt that staff did not treat them empathetically or respectfully ( 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, they found a highly statistically significant difference between women's satisfaction and number of parity, while there is non-statistically significant difference between number of gravida, number of abortion and gestational age with women's satisfaction level (p>0.05). (Elgazzar et al, 2018)…”
Section: Discussionmentioning
confidence: 99%